Perancangan Media Informasi Program Studi Teknik Informatika Dan Sistem Komputer Pada STMIK STIKOM Indonesia Berbasis Animasi 2D - I Nyoman Agus Suarya Putra; I Putu Adi Saputra (Jurnal Bahasa Rupa, 2017)
STMIK STIKOM Indonesia is still using media information about study programs that are static and still can not be conveyed properly. This resulted in the existence of students who moved the study program and specialization when they have undergone lecturing process because they feel unsuitable, and still mistaken the students in distinguishing between study program and specialization. Seeing the problem, STMIK STIKOM Indonesia needs a media information about study program in the form of more practical, interesting, effective and detail, that can be used for media campaign and presentation. 2D animation is suitable as a medium to support the study program information because there are elements of visual, audio, text and color combined so that understanding of a concept or information becomes more easily accepted by the user. After the animation is completed, it is tested by internal STMIK STIKOM Indonesia. The results of these tests show an excellent response from the respondents. Both in terms of visualization, audio, and information from 2D animation as a medium to support information Engineering Studies Program Informatics and Computer Systems at STMIK STIKOM Indonesia.